Behavioral Analysis of Personality, Branding and Emotional State in e-Sports - Halkiopoulos, C.; Gkintoni, E.; Antonopoulou, H.; Skouroliakos, L. (Technium Social Sciences Journal, 2021)
E-sports have grown in popularity on a worldwide scale. Recent assessments place the industry's value at more than $612 million, with operations spanning Europe, North America, and Asia's emerging economies. Nowadays, e-Sports are being hailed as a highly effective marketing channel for businesses. The current study attempted to analyze the personal profiles of e-sports players in order to offer them with marketing privileges that would enable them to promote their companies more effectively. Three self-report questionnaires were used to collect data: the Profile of Mood States, the Eysenck Personality Questionnaire, the Emotional Intelligence Questionnaire, and the Brand Personality Appeal Questionnaire. The collected data were analyzed using appropriate transformations to provide a suitable format for implementing the corresponding machine learning algorithms available in the R software package. The findings of this study demonstrate, among other things, that mood state, emotional intelligence, and brand personality can all serve as critical variables and are prevalent in marketing literature covering a broad range of topics, including evidence that the mood state, emotional intelligence, and brand personality profiles of e-sports players can all serve as significant variables.